The following problems have tripped me up. I can't seem to figure out how to solve them. I've tried, several times, and had my algebra teacher explain them, but I still can't get the answers.

That's no fun, is it? There's nothing to figure out. But I can multiply both sides of the equation by 3 without changing the truth of the equation, right?

3x = 15

And there are a lot of different ways I can write 3:

3 = 1 + 2

= 7 - 4

= -5 + 8

So I can change my equation to look like this:

3x = 15

x(3) = 15

x(7 - 4) = 15

7x - 4x = 15

And since I can add or subtract anything on both sides of an equation without changing the truth of the equation, I can add 4x to both sides:

7x - 4x = 15

7x - 4x ...

Solution Summary

This solution assists to solve for the variable "X" for the problems in a step-by-step process.

... To solve 7 x = 30, we can take the logarithm of each ... then provide a way of moving the variable x from its ... 7. Assume that all variables are positive and multiply ...

...Solve the following problems using the binomial tables: If n=50 and p=.40 ... Let the random variable x be normally distributed with mean 5 and variance 4, Find the ...

... 27 xw10 = 9 * 3 xw10 = 3w 5 3 x. Simplify the following expression as much as possible: Assume that all variables represent positive real numbers. Solution: ...

Multiple Variable Calculus Questions. See attached document. ... Attached in Word. Question 1. Represent the following surfaces in the form z = f(x; y): ... Solution: ...

Multiple Variable Calculus. ... This solution has detailed explanations of questions on finding ... saddle points of functions of two variables, directional derivative ...

... method is an algebraic method for solving systems. ... two equations so that one of the variables cancels ... can use addition or subtraction to eliminate one variable. ...

... The probabilities and statistics for a random variable is determined. Solution to Q1. ∞. ∫ f ( x)dx = 1 . So, (a) To find c, we need to use the property ...

...x −y =3 3x − 2y = 3 Solution: By substitution, we will first use one variable to get the other. We'll use Equation 1 and isolate x. x− y =3 x = 3+ y We ...